Effect of reactants and products in the oxidative coupling of methane over PbO/SiO2 catalysts - Méndez, Xiomara; Finol, Dora; Lugo, Heli (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
The reaction of oxidative coupling of methane (OCM) over PbO/SiO2 catalysts was studied in a flow reactor at 1050 K. The reaction mixture of CH4 and 02, diluted with He, was introduced directly into the reactor, or saturated with steam. Individual reactions of ethane, ethylene and carbon monoxide, in the presence or absence of oxygen, with or without the catalyst, were also investigated. After adding steam to the gas phase, methane conversion and selectivity toward C2 hydrocarbons increased. Ethane dehydrogenation to ethylene occurs through thermal cracking during the OCM reaction. The main source of CO In the OCM reaction is the oxidation of C2H4 in the gas phase. The CO2 formation in the OCM reaction occurs mainly from oxidation of adsorbed CO on the catalyst.